2001
DOI: 10.1074/jbc.c100443200
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein Protects Human Neurons against Bax-mediated Apoptosis

Abstract: The function of the cellular prion protein (PrP) is still poorly understood. We present here an unprecedented role for PrP against Bax-mediated neuronal apoptosis and show that PrP potently inhibits Bax-induced cell death in human primary neurons. Deletion of four octapeptide repeats of PrP (PrP⌬OR) and familial D178N and T183A PrP mutations completely or partially eliminate the neuroprotective effect of PrP. PrP remains anti-apoptotic despite truncation of the glycosylphosphatidylinositol (GPI) anchor signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
272
4
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(298 citation statements)
references
References 40 publications
11
272
4
11
Order By: Relevance
“…Not all mutant PrP alleles scrutinized here lead to loss of protective activity, however, arguing that PrP is not indiscriminately sensitive to perturbation. For example, a Prnp allele impaired in its ability to undergo GPI anchor addition exhibited protective activity comparable with a wt allele, as was also the case for a similar allele tested in the context Bax-initiated apoptosis (26). Although the high frequency at which granule cells are co-transfected when exposed to mixtures of two plasmids indicates that transgene-encoded Dpl and PrP C proteins likely co-exist within the same cells in our paradigm, it is of interest to note that effects in trans (in a cellular sense) have been noted in other paradigms.…”
Section: Activity Determinants In Prp C and Dplmentioning
confidence: 99%
See 2 more Smart Citations
“…Not all mutant PrP alleles scrutinized here lead to loss of protective activity, however, arguing that PrP is not indiscriminately sensitive to perturbation. For example, a Prnp allele impaired in its ability to undergo GPI anchor addition exhibited protective activity comparable with a wt allele, as was also the case for a similar allele tested in the context Bax-initiated apoptosis (26). Although the high frequency at which granule cells are co-transfected when exposed to mixtures of two plasmids indicates that transgene-encoded Dpl and PrP C proteins likely co-exist within the same cells in our paradigm, it is of interest to note that effects in trans (in a cellular sense) have been noted in other paradigms.…”
Section: Activity Determinants In Prp C and Dplmentioning
confidence: 99%
“…The first is defined by the charged motif KKRPKP at the N terminus of mature PrP C (PrP⌬23-28), and the second corresponds to the octarepeat region (PrP⌬51-90). Of note, a similar octarepeat deletion allele failed to protect against Bax-mediated cell death of human neurons (26) and cell death induced by serum deprivation of a Prnp 0/0 neuronal cell line (57,58). Missense mutations substituting octarepeat histidine residues for glycine (PHGG(G/ S)WGQ 4 3 PGGG(G/S)WGQ 4 ) also inactivated the protective effect of PrP C (Fig.…”
Section: Activity Determinants In Prp C and Dplmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuwahara, et al previously reported that hippocampal neuronal cells from PrP-/-mice easily undergo apoptosis after withdrawal of serum, which can be prevented by either re-introduction of PrP C or by expressing the anti-apoptotic protein, Bcl-2 (46). Bounhar, et al also showed that PrP C protected human primary neurons from the apoptosis induced by the pro-apoptotic protein Bax (47). It is therefore suggested that PrP C might be an anti-apoptotic protein while PrPLP/Dpl might be pro-apoptotic.…”
Section: Cis-and Trans-neuroprotective Function Of Prp Against Prplp/dplmentioning
confidence: 96%
“…Identifying the function of PrP C may provide important clues to pathogenic mechanisms, because there is evidence that PrP C , in addition to serving as a precursor of PrP Sc , acts as a mediator of PrP Sc -induced neurotoxicity (3)(4)(5). A variety of functions have been proposed for PrP C , including roles in metal ion trafficking (6), protection from oxidative stress and apoptosis (7,8), cell adhesion (9), and transmembrane signaling (10). However, the evidence in favor of each of these hypothesized functions is not definitive.…”
mentioning
confidence: 99%